A Short Note on Short Notes - Donovan, Stephen K. (Journal of Scholarly Publishing, 2012)
This is a short note. It is tightly focused and brief; its message can be rapidly assimilated by the reader. Like Robert Boyle in the seventeenth century, I bemoan the modern focus on lengthier publications, possibly the result of pressure from managers on academics to encourage them to publish long and ‘significant’ papers in leading journals. Yet, the most important paper published in the life sciences during the twentieth century was only two pages long.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzEzOC9qc3AuNDMuNC40NDA